Asian worldviews : religions, philosophies, political theories - Raud, Rein (Hoboken, NJ : Wiley-Blackwell, 2021)
'The aim of this book is to acquaint its reader with the rich thought traditions of Asia (India, China, Japan, Korea, Tibet and South-East Asia), which have mutually influenced each other throughout history and consequently share large parts of their intellectual heritage. It can serve both as an introductory textbook for the future specialist and as a source of background knowledge for those whose primary interest lies outside Asian studies, be it religious studies, Western philosophy, political science or anything else. No previous knowledge of the history or cultures of this region is presupposed, entanglement in specific debates is avoided and names and terms have been kept to the minimum. If you think that an educated person anywhere in the world should know who are St.Augustine, Luther and Mother Theresa, or Aristotle, Kant and Wittgenstein, or Machiavelli, Rousseau and Marx, or what is the meaning of'cardinal sin', cogito and'separation of powers', the names and terms printed bold in this book are those you should be familiar with from a range of Asian points of view. I have done my best to keep the scope of the book equally balanced throughout and to maintain a more or less similar level of coverage in all areas. The book thus addresses all teachings, schools and individuals that have usually been included in the range of such introductory intellectual histories. However, the reader will notice that some authors and ideas not always present in similar overviews, such as feminist theorists, have been given more space here than has been customary up to now'--
Includes index.
Keywords: Asia -- Intellectual life